'Learn or die': the development of an assessment framework for SME entrepreneurial learning programmes. (14th April 2011) - Bergh, Pontus; Jacobsson, Mattias
The unique features of entrepreneurial learning, which involves multiple dimensions, are not easily captured and today few appropriate assessment frameworks exist. The aim of this paper is, therefore, to develop an assessment framework for entrepreneurial learning and empirically illustrate its potential on a specific small- and medium-sized enterprises (SME) learning programme. Based on a survey of owners/managers who took part in the government-supported learning programme, krAft, an exploratory factors analysis and a regression analysis were conducted. This paper proposes a two-dimensional framework of cognitive and social/emotional learning outcomes where both are strongly correlated to internal efficiency but only the social/emotional outcomes are correlated to external effectiveness. This paper, therefore, concludes that the mere focus on cognitive learning outcomes is not enough to successfully act upon business opportunities. Hence, the social/emotional learning dimension is of great importance, and should be utilised, in the development of arranged SME learning groups.